Let's denote the change in the concentration of N, H, and NH as x, 3x, and 2x, respectively, as the reaction proceeds. At equilibrium, the concentrations will be as follows:[N] = 0.10 - x[H] = 0.20 - 3x[NH] = 2xNow, we can use the equilibrium constant expression to find the value of x:$$K_c = \frac{[\mathrm{NH_3}]^2}{[\mathrm{N_2}][\mathrm{H_2}]^3}$$Substitute the equilibrium concentrations:$$5.6 \times 10^{-5} = \frac{ 2x ^2}{ 0.10 - x 0.20 - 3x ^3}$$Solving for x is quite challenging algebraically. However, we can make an assumption that x is small compared to the initial concentrations of N and H, which allows us to simplify the equation:$$5.6 \times 10^{-5} = \frac{4x^2}{ 0.10 0.20 ^3}$$Now, solve for x:$$x^2 = \frac{5.6 \times 10^{-5} \times 0.10 \times 0.20^3}{4}4}$$$$x^2 = 1.792 \times 10^{-7}$$$$x = \sqrt{1.792 \times 10^{-7}}$$$$x = 1.34 \times 10^{-4}$$Now we can find the equilibrium concentrations:[N] = 0.10 - x = 0.10 - 1.34 10 0.0999 M[H] = 0.20 - 3x = 0.20 - 3 1.34 10 0.1996 M[NH] = 2x = 2 1.34 10 2.68 10 MSo, the equilibrium concentrations are approximately 0.0999 M for N, 0.1996 M for H, and 2.68 10 M for NH.